Notes to literature - Adorno, Theodor W., 1903-1969 (European perspectives., 2019)
Notes to Literature is a collection of the great social theorist Theodor W. Adorno's essays on such writers as Mann, Bloch, Goethe, and Benjamin, as well as his reflections on a variety of subjects. This edition presents this classic work in full in a single volume, with a new introduction by Paul Kottman.